Agreement between symptom surveys, physical examination procedures and electrodiagnostic findings for the carpal tunnel syndrome - Homan, M. M.; Franzblau, Alfred; Werner, Robert A.; Albers, J. W.; Armstrong, Tom J.; Bromberg, M. B. (Scandinavian Journal of Work, Environment & Health, 1999)
' ' OBJECTIVES ': 'The goal of this study was to evaluate the concordance between various clinical screening procedures for carpal tunnel syndrome.' ' METHODS ': 'The subject population consisted of 824 workers from 6 facilities. The evaluated procedures included bilateral sensory nerve conduction testing, physical examinations, and symptom surveys, including hand diagrams. The agreement between the outcomes of various combinations of these procedures was assessed by determining the kappa coefficient.' ' RESULTS ': 'There was relatively poor overlap between the reported symptoms, the physical examination findings, and the electrodiagnostic results consistent with carpal tunnel syndrome. Overall, only 23 out of 449 subjects (5%) with at least 1 positive finding met all 3 criteria (symptoms, physical examination findings, and electrophysiological results consistent with carpal tunnel syndrome) for the dominant hand. The screening procedures showed poor or no agreement with kappa values ranging between 0.00 and 0.18 for all the case definitions evaluated for carpal tunnel syndrome.' ' CONCLUSION ': 'The poor overlap between the various screening procedures warns against the use of electrodiagnostic findings alone without the symptom presentation being considered. The results of this study also point to a need for the further development and evaluation of methods for detecting carpal tunnel syndrome.
Keywords: carpal compression test; discomfort survey; hand diagram; kappa coefficient; nerve conduction testing; Phalen's test; surveillance; Tinel's test